Synthesis, characterization and biological activity of bis[3-ethyl-4-aryl-5-(2-methoxypyridin-5-yl)-1-propyl-1, 3-dihydro-2H-imidazol-2-ylidene]gold(i) complexes. Issue 12 (10th March 2021) - Gallati, Caroline Marie; Goetzfried, Sina Katharina; Ortmeier, Anna; Sagasser, Jessica; Wurst, Klaus; Hermann, Martin; Baecker, Daniel; Kircher, Brigitte; Gust, Ronald
Abstract : A series of bis[3-ethyl-4-aryl-5-(2-methoxypyridin-5-yl)-1-propyl-1, 3-dihydro-2 H -imidazol-2-ylidene]gold(i ) complexes was synthesized and evaluated for the anti-cancer properties in sensitive and resistant ovarian carcinoma and leukemia cell lines. Abstract : A series of bis[3-ethyl-4-aryl-5-(2-methoxypyridin-5-yl)-1-propyl-1, 3-dihydro-2 H -imidazol-2-ylidene]gold(i ) complexes (2a–f ) containing methyl, fluoro or methoxy substituents at various positions in the 4-aryl ring was synthesized and evaluated for their anti-cancer properties in A2780 (wild-type and Cisplatin-resistant) ovarian carcinoma as well as LAMA 84 (imatinib-sensitive and -resistant) and HL-60 leukemia cell lines. The bis-NHC gold(i ) complexes were more active compared to their related mono-NHC gold(i ) analogues and reduced proliferation and metabolic activity in a low micromolar range. With the exception of 2d (3-F), the compounds displayed higher potency than the established drugs Auranofin and Cisplatin. The lack of effects against non-cancerous lung fibroblast SV-80 cells indicated a high selectivity towards tumor cells. All tested complexes generated reactive oxygen species in A2780cis cells; however, the induction of apoptosis was very low. Furthermore, thioredoxin reductase is not the main target of these complexes, because its inhibition pattern did not correlate with their biological activity.